Joint Action Coordination in 2½- and 3-Year-Old Children - Meyer, Marlene; Bekkering, Harold; Paulus, Markus; Hunnius, Sabine (Frontiers in Human Neuroscience, 2010)
When acting jointly with others, adults can be as proficient as when acting individually. However how young children coordinate their actions with another person and how their action coordination develops during early childhood is not well understood. By means of a sequential button-pressing game, which could be played jointly or individually, the action coordination of 2½- and 3-year-old children was examined. Performance accuracy and variability of response timing were taken as indicators of coordination ability. Results showed substantial improvement in joint action coordination between the age of 2½- and 3, but both age groups performed equally well when acting individually. Interestingly, 3-year-olds performed equally well in the joint and the individual condition, whereas 2½-year-olds did not yet show this adult-like pattern as indicated by less accurate performance in the joint action. The findings suggest that in contrast to 3-year-olds, 2½-year-olds still have difficulties in establishing well-coordinated joint action with an adult partner. Possible underlying cognitive abilities such as action planning and action control are discussed.